Comparison of the Effect of Custom Insole With CAD-CAM and Conventional Insole on FAOS Questionnaire Subscales in Patients With Plantar Fasciitis - Sara Shojaie; Mahmood Bahramizade; Monireh Ahamadi Bani; Mohsen Movahedi Yeganeh; Mohammad Ebrahimi Moosavi (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: One of the significant causes of foot pain is plantar fasciitis. The use of medical insoles is a conventional treatment for this condition. The purpose of this study was to compare the effect of the customized insole with the CAD-CAM and conventional insole on pain, symptoms, daily activity, exercise and recreational activity, and quality of life in patients with PF. Materials & Methods: This quasi-experimental study was performed on 14 patients with plantar fasciitis (five women and nine men) with the mean age of 40 years. Fourteen patients have been diagnosed with orthopedic pain after being diagnosed with plantar fasciitis according to inclusion criteria. Diagnosis of the complication of plantar fasciitis by orthopedic physician, Patients with flexible flat foot. No neurological disorders or any foot pathology such as diabetes and osteoarthritis. Patients were randomly assigned into two groups of 7 using customized insole with CAD-CAM and conventional (prefabricated) insole. From the outset it was found to be one of two types of insole to be studied: first the patient was given a CNC insole, and the other 13 patients received the same insole and divided into two groups. The instrument of this study was the FAOS questionnaire (foot and ankle outcomes) which measures the five variables of pain, symptoms, daily activities, sports and recreational activities, and quality of life. Both groups completed the questionnaire before using the insole and again after six weeks. Compressive scan of both groups was accomplished using EMED foot pressure system. The custom-made insole was designed using Rhino Cross software and then shaved using EVA foam blocks with 50% shore using a CNC machine. In the conventional insoles group, patients received conventional polyurethane insoles based on the length measurements of the single leg. Patients completed the questionnaire again after six weeks. Data were analyzed by SPSS software v. 22. After checking the normality of the data by Shapiro-Wilk test, non-parametric Mann-Whitney and Wilcoxon tests were used to analyze the data. Results: In the pre-intervention phase, there was no significant difference in pain, symptoms, daily activities, recreational-sports activities, and quality of life in the two groups, and the two groups were homogeneous. After six weeks, there was a significant difference between the two groups in the FAOS questionnaire (P<0.05). There was no significant difference between the two groups in pain score, symptoms, daily activities, recreational-sport activities, and quality of life (P <0.05). Conclusion: According to the results of this study, both customized insoles with CAD-CAM and conventional insoles are effective in improving FAOS questionnaire subscales. There was no significant difference in the impact between the two types of insoles in foot and ankle.